New Distribution Centre Locations for a growing retail company in Thailand: The case study of Siam Global House Plc. - Suriyawanakul, Kriangkai (2010)
Logistics and distribution management is a very important topic for many industries for the last couple of decades. Many companies have structured and redesigning their logistics network to compete in the market. Among all, warehouse location decision is one of the most important elements as it is learnt that good location decisions can save companies millions every year.